Sistema de virtualización centralizado como soporte para el desarrollo y producción científica mediante la herramienta de virtualización proxmox dentro de la carrera de ingeniería en informática y sistemas computacionales - Guanoluisa Arciniega, Mauro Omar (2016)
In this project the tool will be used virtualization compute Proxmox to virtualize and centralize two application servers one on the Windows platform and another on Linux with the operating systems Windows Server 2012 and Ubuntu Server 14.04 LTS in which will be installed and configured several services such as ssh, FTP, IIS, Tomcat, among others, this is intended to provide to a career in Engineering in Computer Science and Computer Systems a means to host and publish computer projects based on the development of software, with the purpose of evaluating the different functionalities and the performance of each project.In the technical scientific foundation will detail the bibliographic information collected from several sources as are: scientific articles, theses, books, official page of Proxmox and online sources, the bibliographic sources used will be listed in the present document in the point respective.